Women's entrepreneurship policy : a global perspective - Henry, Colette; Coleman, Susan; Lewis, Kate V. (Edward Elgar Publishing, 2023)
"Bringing together scholars from around the world, this book provides extensive coverage of the academic literature and research on women's entrepreneurship policy. Featuring contributions from members of the Global Women's Entrepreneurship Policy Research Network, the book explores and critiques contemporary policy instruments while also pointing toward potential policy solutions. Chapters aim to deepen understanding of women's entrepreneurship policy and raise awareness among policy makers, programme managers and academics of the dangers associated with gender-blind entrepreneurship policies. The book concludes that 'one size fits all' policies that ignore the gender dimension do not support women entrepreneurs effectively. Research-based and international in approach, Women's Entrepreneurship Policy will be a useful guide for academics and advanced students in the areas of entrepreneurship, gender and management, diversity and management, and international business. It will also be beneficial for policy makers and those involved in designing and delivering women's entrepreneurship programmes"--